Product Quality, Service Quality, Price, and Location Influence Towards Coffee Shop Customer’s Satisfaction - Salsabillah, Ayu Riska; Bahari K, Habib; Mustikasari, Faranita (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study investigates the influence of product quality, service quality, price, and location on customer satisfaction in coffee shops. The coffee shop industry is highly competitive, with numerous establishments vying for customer loyalty. Understanding the factors that contribute to customer satisfaction is crucial for the success of coffee shop businesses. To achieve this, a comprehensive survey was conducted, gathering responses from a diverse sample of coffee shop customers. The research findings indicate that product quality, service quality, price, and location significantly impact customer satisfaction. High-quality coffee products, exceptional service, reasonable pricing, and convenient locations were found to positively influence customer satisfaction. These results provide valuable insights for coffee shop owners and managers, enabling them to make informed decisions and tailor their strategies to enhance customer satisfaction and ultimately, the success of their businesses.